Interstellar dimethyl ether gas-phase formation: a quantum chemistry and kinetics study. Issue 3 (27th October 2018) - Skouteris, Dimitrios; Balucani, Nadia; Ceccarelli, Cecilia; Faginas Lago, Noelia; Codella, Claudio; Falcinelli, Stefano; Rosi, Marzio
ABSTRACT: Dimethyl ether is one of the most abundant interstellar complex organic molecules. Yet its formation route remains elusive. In this work, we have performed electronic structure and kinetics calculations to derive the rate coefficients for two ion–molecule reactions recently proposed as a gas-phase formation route of dimethyl ether in interstellar objects, namely CH3 OH + CH3 OH$_2^+$  → (CH3 )2 OH + + H2 O followed by (CH3 )2 OH + + NH3  → CH3 OCH3 + NH$_4^+$ . A comparison with previous experimental rate coefficients for the reaction CH3 OH + CH3 OH$_2^+$ sustains the accuracy of the present calculations and allows a more reliable extrapolation at the low temperatures of interest in interstellar objects (10–100 K). The rate coefficient for the reaction (CH3 )2 OH +  + NH3 is, instead, provided for the first time ever. The rate coefficients derived in this work essentially confirm the prediction by Taquet, Wirström & Charnley concerning dimethyl ether formation in hot cores/corinos. Nevertheless, this formation route cannot be efficient in cold objects (like pre-stellar cores) where dimethyl ether is also detected, because ammonia has a very low abundance in those environments.